Kinetic Study of Anaerobic Digestion of Ketchup Industry Wastewater in a Three-stages Anaerobic Baffled Reactor (ABR) - Indro Sumantri; Budiyono Budiyono; Purwanto Purwanto (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
The anaerobic digestion of the ketchup industry’s wastewater in a three-stage 60 L capacity baffled reactor has been studied. The effect of concentrations of the initial chemical oxygen demand (2727.3-12086.7 mg/L), on the ABR performance and kinetic models were investigated. The ABR performance was evaluated by measuring the concentrations of each compartment of the COD, calculating its percentage removal, and the acquired data were fitted to the kinetic models. From the initial input, the three-stage ABR successfully removed 90 % of COD, for the initial COD until the concentration was 5324.6 mg/L it achieved stationary phase with HRT 5-10 days, while for initial COD until the concentration was 12086.7 mg/L is attained, the stationary was at 10 days. The kinetic model of second order Grau was suitable for the data, with k2 of 0.6061 d-1 and R2 of 0.9955.